Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2008
DOI: 10.1111/j.1365-2753.2007.00874.x
|View full text |Cite
|
Sign up to set email alerts
|

General practitioners’ assessment of risk of violence in their practice: results from a qualitative study

Abstract: A schema of factors involved in GPs' assessment of risk of violence is presented. An appreciation of these will be of clinical and policy importance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
12
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 18 publications
(21 reference statements)
1
12
0
Order By: Relevance
“…The concern regarding personal safety has previously been reported in qualitative studies on GPs' experiences of violence in UK and Australia [30,31]. One of these studies was conducted 20 years ago [30], indicating that personal safety is no new worry for GPs.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The concern regarding personal safety has previously been reported in qualitative studies on GPs' experiences of violence in UK and Australia [30,31]. One of these studies was conducted 20 years ago [30], indicating that personal safety is no new worry for GPs.…”
Section: Discussionmentioning
confidence: 98%
“…Reported prevalence of experienced violence among GPs ranges from 21% to 83% depending on methodology and geographical area studied [34-41]. The apprehension about work-related violence has been found to be particularly high in out-of-hours services [31,42-44]. As most papers on work-related violence in general practice have pointed out, this might have serious consequences for a viable after-hours primary healthcare service.…”
Section: Discussionmentioning
confidence: 99%
“…10 Moreover, discrimination between subtle stimuli and integrative processing are central to clinical skills such as ultrasonography 11 and are highly valued [12][13][14] by the patient-centered clinical method, which uses patient experience to help guide clinical interactions and shared decision making. Nevertheless, physicians-unlike nurses 15 -have frequently been reluctant to publicly acknowledge using their own intuition in clinical decision-making; 16 and they have been even quieter in acknowledging their need to take account of patient intuition in decision-making.…”
mentioning
confidence: 99%
“…Although data from the 2007 National Physicians' Survey (NPS) indicates that most family physicians are satisfied with their clinical practices, studies in several countries have reported that violence in family practice towards physicians is a serious problem [1–11]. In New Zealand, it was reported that on an annual basis, 15% of general practioners were verbally abused, 4% were assaulted, and 2% were stalked [8].…”
Section: Introductionmentioning
confidence: 99%
“…Researchers in Australia and the UK have recently examined violence against physicians however few have examined the issue in Canada [1, 17]. Canadian studies that have been undertaken are at least a decade old and are limited in scope.…”
Section: Introductionmentioning
confidence: 99%